Evaluation of Interleukin-6 and its Association with the Severity of Disease in COVID-19 Patients - Sudhir Bhandari; Govind Rankawat; Ajeet Singh; Dileep Wadhwani; Bhoopendra Patel (Indian Journal of Medical Specialities)
Background: The present study was undertaken to determine the levels of interleukin-6 (IL-6) and evaluate its association with clinical presentation, severity, radiological imaging, management, and outcome in coronavirus disease (COVID-19) infection. Methods: The present study included 132 admitted COVID-19 patients, categorized into three groups. Group 1 had IL-6 within the normal reference range, Group 2 had IL-6 raised up to ten times the upper normal limit (UNL), and Group 3 had IL-6 level raised > ten times the UNL. The patient's data concerning medical history, clinical manifestations, laboratory findings, radiological imaging, management, and outcome were extracted from their medical records for subsequent evaluation, interpretation, and association among the groups. Results: COVID-19 patients with raised IL-6 levels exhibited frequent symptomatic presentations, severity, and critical illness, especially with extremely high IL-6 levels (P < 0.001). Radiological findings in terms of a digital chest radiograph and high-resolution computed tomography (CT) chest indicated severe lung involvement in patients with extremely high IL-6 levels (P < 0.05). The majority of patients with extremely raised IL-6 levels were associated with the classic COVID-19 CT images (P = 0.014). Patients with extremely raised IL-6 levels required intensive treatment as compared to normal IL-6 group in terms of tocilizumab therapy (P = 0.008), noninvasive ventilation (P < 0.001), and intensive care unit care (P = 0.009) associated with higher mortality (P = 0.046). Conclusion: Raised IL-6 levels in COVID-19 patients should be considered a risk factor for the severity of the disease, inflammatory storm, and rapid pulmonary invasion. There is an urgent need for establishing a treatment protocol in patients with extremely raised IL-6 levels.